Persepsi Masyarakat Islam Kejawen di Kabupaten Cilacap terhadap Implementasi Pasal 7 Ayat 1 Undang-Undang Nomor 16 Tahun 2019 tentang Perubahan Usia Perkawinan - Muchimah Muchimah; Mabaroh Azizah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This article discusses the perceptions of the Javanese Islamic community regarding the implementation of Article 7 Paragraph 1 of Law Number 16 of 2019 concerning changes in the age of marriage. This research originated from a judicial review filed by the Indonesian Child Protection Commission (KPAI), the Constitutional Court. The decision decided that Article 7 paragraph (1) is as long as the phrase